The IPCC and the new map of science and politics. (21st August 2018) - Beck, Silke; Mahony, Martin
Abstract : In this study, we review work which seeks to understand and interpret the place of the Intergovernmental Panel on Climate Change (IPCC) within the science and politics of climate change in the context of a post‐Paris polycentric governance regime and the culture of "post‐truth" politics. Focusing on studies of how the IPCC has sought to maintain a boundary between the scientific and the political, we offer an historical account of "boundary work" within the IPCC which is instructive for thinking, in an anticipative mode, about emerging and likely challenges to the IPCC's position as a science–policy boundary organization. We suggest that the relationships between climate science and policy are undergoing fundamental transformation in light of the Paris Agreement, and contend that the IPCC will need to be nimble and reflexive in meeting new challenges. Growing calls for more "solution‐oriented" assessment question the IPCC's positioning at the science—politics boundary, where it can function to put some policy options on the table, while obscuring others. Recent controversies over proposed mitigation solutions are indicative of likely future challenges. We suggest that by adopting a mode of "responsible assessment, " the IPCC can continue to exercise its world‐making power in a relevant and legitimate fashion. This article is categorized under: Social Status of Climate Change Knowledge > Climate Science and Decision Making